Le “scientific questions” nella dinamica tra discrezionalità giurisdizionale e legislativa. Uno studio comparato sul giudizio delle leggi scientificamente connotate nelle giurisdizioni nazionali, sovranazionale e internazionali (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The scientific content of question that national, supranational and international courts increasingly face in exercising their function may influence the traditional relationship between judicial and legislative discretionary power. Through a comparative analysis of decisions derived from Constitutional, Supreme, European and International Courts, the article provides for a systematization of the different attitudes that jurisdictions may adopt before “scientific questions”. Special emphasis will be dedicated to the approach concretely implemented by courts, within a classification that goes from self-restraint to judicial activism.
Keywords: Biolaw; Comparative law; Pluralism; Jurisdiction; Scientific questions